Acute anterior uveitis is associated with depression and reduction of general health. Issue 3 (19th January 2013) - Maca, Saskia M; Wagner, Julia; Weingessel, Birgit; Vécsei-Marlovits, Pia V
Abstract : Aims: This study explored the association of active acute anterior uveitis (AAU) with depressive feelings and patients' general health. Methods: This case-control study comprised 80 participants: 35 patients with an active case of AAU and 45 healthy peers were analysed to compare their depressive moods (Beck depression inventory (BDI), Zerssen Mood Scale (ZMS)) and general health (Short form-8 health survey (SF8)). Furthermore, patients were questioned regarding the presence of distress, occupational satisfaction and impairment in performing daily life tasks. Results: During an acute attack, AAU patients were shown to suffer from depressive moods more often than their healthy peers (BDI 54% vs 9%, respectively; ZMS 2.7-fold shift in mood levels towards depression) and experienced a reduction in mental and physical scores (SF8). Patients felt impaired reading (94%), driving (69%) and working (69%). In all, 74% of the patients believed that distress was a probable trigger. Lack of occupational satisfaction was associated with a persistence of depressive feelings and a reduction in physical health. Conclusions: AAU patients exhibited a significant psychopathology towards depression, a reduction of general health and impairment of performing daily life tasks. Patients who were unsatisfied at work seemed to suffer even more. The results underline the importance of offering psychological support to the patients and providing information to patients and close social contacts.